Efficient White Electrochemiluminescent Emission From Carbon Quantum Dot Films - Adsetts, Jonathan Ralph; Zhang, Ruizhong; Yang, Liuqing; Chu, Kenneth; Wong, Jonathan Michael; Love, David A.; Ding, Zhifeng (Frontiers in Chemistry, 2020)
Carbon quantum dots (CQDs) were manufactured from citric acid and urea in a gram-scale synthesis with a controlled size range between 1.5 - 23.8 nm. The size control was realized by varying volume of the precursor solution in a hydrothermal synthesis method. The prepared CQDs were investigated using electrochemiluminescence (ECL) spectroscopy at interfaces of their electrode films and electrolyte solution containing coreactants rather than conventional optoelectronic tests, providing an in-depth analysis of light-emission mechanisms of the so-called half-cells. ECL from the CQD films with TPrA and K2S2O8 as coreactants provided information on the stability of the CQD radicals in the films. It was discovered that CQD•- has a powerful electron donating nature to sulfate radical to generate ECL at a relative efficiency of 96% to the Ru(bpy)3Cl2/K2S2O8 coreactant system, indicating a strong performance in light emitting applications. The smaller the CQD particle sizes, the higher the ECL efficiency of the film interface, most likely due to the increased presence of surface states per mass of CQDs. Spooling ECL spectroscopy of the system revealed a potential-dependent light emission starting from a deep red color to blue-shifted intensity maximum, cool bright white emission with a correlated color temperature of 3200 K. This color temperature is appropriate for most indoor lighting applications. The above ECL results provide information on the performance of CQD light emitters in films, permitting preliminary screening for light emitting candidates in optoelectronic applications. This screening has revealed CQD films as a powerful and cost-effective light emitting layer toward lighting devices for indoor applications.